Peripheral, Central, and Cross Sensitization in Endometriosis-Associated Pain and Comorbid Pain Syndromes - McNamara, Helen C.; Frawley, Helena C.; Donoghue, Jacqueline F.; Readman, Emma; Healey, Martin; Ellett, Lenore; Reddington, Charlotte; Hicks, Lauren J.; Harlow, Keryn; Rogers, Peter A. W.; Cheng, Claudia (Frontiers in Reproductive Health, 2021)
Endometriosis is a complex, estrogen dependent disorder with a cumulative prevalence of 11%. Symptoms of endometriosis include infertility and pain. Endometriosis-associated pain is experienced as dysmenorrhea, cyclical pain related to organ function including dysuria, dyschezia and dyspareunia, and persistent pelvic pain. Pain symptomatology correlates poorly with the extent of macroscopic disease. The complexity of endometriosis-associated pain is a product of the different mechanisms involved. In addition to the local effects of disease, endometriosis-associated pain develops as a product of peripheral sensitization, central sensitization and cross sensitization. Endometriosis-associated pain is further contributed to by comorbid pain conditions, such as bladder pain syndrome, irritable bowel syndrome, abdomino-pelvic myalgia and vulvodynia. This article will review endometriosis-associated pain, its mechanisms, and its comorbid pain syndromes with a view to aiding the clinician in navigating the literature and terminology of pain and pain syndromes. Limitations of our current understanding of endometriosis-associated pain will be acknowledged. Where possible, commonalities in pain mechanisms between endometriosis-associated pain and comorbid pain syndromes will be highlighted.